Characteristics of turion development in two aquatic carnivorous plants: Hormonal profiles, gas exchange and mineral nutrient content - Lubomír Adamec; Lenka Plačková; Karel Doležal (Plant Direct, 2024)
Abstract Turions are vegetative, dormant, and storage overwintering organs formed in perennial aquatic plants in response to unfavorable ecological conditions and originate by extreme condensation of apical shoot segments. The contents of cytokinins, auxins, and abscisic acid were estimated in shoot apices of summer growing, rootless aquatic carnivorous plants, Aldrovanda vesiculosa and Utricularia australis, and in developing turions at three stages and full maturity to reveal hormonal patterns responsible for turion development. The hormones were analyzed in miniature turion samples using ultraperformance liquid chromatography coupled with triple quadrupole mass spectrometry. Photosynthetic measurements in young leaves also confirmed relatively high photosynthetic rates at later turion stages. The content of active cytokinin forms was almost stable in A. vesiculosa during turion development but markedly decreased in U. australis. In both species, auxin content culminated in the middle of turion development and then decreased again. The content of abscisic acid as the main inhibitory hormone was very low in growing plants in both species but rose greatly at first developmental stages and stayed very high in mature turions. The hormonal data indicate a great strength of developing turions within sink–source relationships and confirm the central role of abscisic acid in regulating the turion development.